(untitled) (International Journal of Engineering and Computer Science, 2014)
Wireless communication is a communication between more than one points without the use of any interconnection networks. It permits the long range communication. The best example of wireless communication is radio system. In early days most of the systems transmit the analog signals. But now a days ,radio systems transmit the digital datas composed of binary bit streams which are obtained directly from the signals or by digitizing the analog signals. The architecture used in this type of communication is multimode multichannel RF transmitter and receiver using Delta sigma modulator. This paper deals about the single channel and multichannel transmitter sections .These two architectures are implemented using VHDL programming language.